Kyrgyz Republic : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility, and Request for Modification of Performance Criteria-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses the Kyrgyz Republic's Third Review under the Three-Year Arrangement under the Extended Credit Facility (ECF) and the Request for Modification of Performance Criteria (PCs). Program conditionality has been broadly met. All end-June 2016 quantitative PCs and indicative targets have been met. All but two structural benchmarks were met. The review of subsidies was not completed on time owing to limited capacity. The authorities are requesting modification of PCs to reflect the revised macroeconomic outlook and the availability of the fourth disbursement on completion of the review. The IMF staff supports completing the third review of the authorities' program under the ECF arrangement.